Analysis of the Implementation of Training Management in Educational Institutions: A Literature Research Approach to Improve Performance and Competence - Agung Muhammad Nur (CV. ITTC INDONESIA, 2024)
This study investigates the implementation of training management in educational institutions through a desk research approach. The main focus was to identify key issues such as management support, participant involvement, organizational culture, and program evaluation. The research method involved analyzing literature from books, journals and related documents to gain in-depth understanding. The analysis showed that strong management support is essential for the success of training programs, with adequate resource allocation and commitment to human resource development. The active involvement of participants is considered crucial in ensuring the relevance and sustainability of the program. An organizational culture that promotes continuous learning also makes an important contribution to the professional development and performance improvement of education institutions.